Toxicity of Surface Water Contamianted with Arthropogenic Pollutants to Micro-Crustacean, Daphnia magna - Sơn, Đào Thanh; Liên, Nguyễn Thị Phương; Thanh, Võ Thị Kiều; Hiền, Tô Thị; Phú, Nguyễn Lý Sỹ; Thanh, Đào Công; Lưu, Phạm Thanh (VNU Journal of Science: Earth and Environmental Sciences; Vol 31 No 3, 2015)
Arthropogenic pollutants are among the most serious problems to aquatic environment. They not only cause the water quality degradation but also induce severe impacts on aquatic organisms. In this study, we investigated the negative effects of surface water contaminated with pollutants from human activities collected from Xuan Huong lake, Da Lat city, on life history traits of Daphnia magna , over a period of 14 days. The animal was incubated in medium containing the contaminated surface water at eight different concentrations from 0.05% to 25% (v/v) in the laboratory conditions. The results showed that the contaminated surface water seriously and negatively influenced on the survival of Daphnia , causing the decease of 27-100% of the exposed organism population, and the higher surface water concentration the animal exposed, the higher mortality it was. The contaminated water also delayed the maturity age of the tested organisms, around 3-8 days compared to the control. The maturity postponement was concentration dependent. Besides, the fecundity of the Daphnia exposed to the contaminated water was inhibited or strongly reduced. Heavy metals and pesticides in the surface water should be the main factors inducing the potent toxic impacts on the test organisms. Therefore, pollutants in the effluents from human activities at Da Lat city should be effectively treated before discharged in order to protect the aquatic environment, biological resources and ecosystem. Keywords : contaminated surface water, heavy metals, pesticides, Daphnia magna , life history traits